2020
DOI: 10.37398/jsr.2020.640112
|View full text |Cite
|
Sign up to set email alerts
|

Non-random Distribution of Heterozygous Inversions in a Natural Population of Drosophila malerkotliana

Abstract: Drosophila malerkotliana is one of the members of the Drosophila bipectinata species complex. It has been moderately analyzed for its genetic characteristics, especially for the purpose of phylogenetic relationships with other species of this complex. It is chromosomally polymorphic due to the presence of paracentric inversions. In this article, the chromosomal polymorphism of a natural population, sampled from Bilaspur (Chhattisgarh) has been reported. More than five hundred third instar larvae were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Among the Drosophila species that occur most commonly in the Indian subcontinent, this species is highly prevalent. A large number of studieshave been conducted in D. malerkotliana related to inversion and allozyme polymorphisms to observe genetic characteristics of its populations (Parkash& Gill, 1980;Singh, 2019;Singh & Singh, 2020;2022;Trehan& Gill, 1985;1986;.Due to its differential distribution between the northern and southern parts of our country, environmental factors, especially temperature fluctuations, are thought to play a role in that distribution (Singh, 2019;Singh & Singh, 2001). In a study conducted by Singh & Singh (2022), it has been found that the level ofheterozygosity increases from north India to south India.In one of the studies, Singh & Singh (2020) haveshown that there exists high level of genetic variation (0.603) in the same population (being used for this experiment).…”
Section: Introductionmentioning
confidence: 99%
“…Among the Drosophila species that occur most commonly in the Indian subcontinent, this species is highly prevalent. A large number of studieshave been conducted in D. malerkotliana related to inversion and allozyme polymorphisms to observe genetic characteristics of its populations (Parkash& Gill, 1980;Singh, 2019;Singh & Singh, 2020;2022;Trehan& Gill, 1985;1986;.Due to its differential distribution between the northern and southern parts of our country, environmental factors, especially temperature fluctuations, are thought to play a role in that distribution (Singh, 2019;Singh & Singh, 2001). In a study conducted by Singh & Singh (2022), it has been found that the level ofheterozygosity increases from north India to south India.In one of the studies, Singh & Singh (2020) haveshown that there exists high level of genetic variation (0.603) in the same population (being used for this experiment).…”
Section: Introductionmentioning
confidence: 99%